2021
DOI: 10.3390/nu13062078
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Small-Molecule Oligopeptides Isolated from Tilapia Fish Scale on Ethanol-Induced Gastroduodenal Injury in Rats

Abstract: Peptic ulcer has a serious impact on people’s health around the world, and traditional medicines can cause adverse reactions. This study investigated the protective effects of tilapia collagen oligopeptides (TCOPs) on gastroduodenal injury. Seventy-two specific pathogen-free (SPF) male Sprague Dawley (SD) rats were randomly divided into six groups according to body weight: normal control group, ethanol group, whey protein group (500 mg/kg BW), and three TCOPs dose groups (250, 500, 1000 mg/kg BW). After intrag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
(59 reference statements)
2
2
0
Order By: Relevance
“…Our results showed that gastric pH decreased significantly in the ulcer group. These results agreed with previous studies [ 39 , 40 ]. On the contrary, treatment with Aloe vera increased gastric pH significantly due to inhibition of acid secretion.…”
Section: Discussionsupporting
confidence: 94%
“…Our results showed that gastric pH decreased significantly in the ulcer group. These results agreed with previous studies [ 39 , 40 ]. On the contrary, treatment with Aloe vera increased gastric pH significantly due to inhibition of acid secretion.…”
Section: Discussionsupporting
confidence: 94%
“…Mechanistically, our data indicated WIRS intake made the anti-apoptosis gene Bcl-2 down-regulated markedly driven by ROS and pro-inflammatory signals. In this circumstance, the restriction to the apoptotic protein Bax was limited, which in turn led to the mitochondrial escape of cytochrome C and subsequently activated Caspase-3, which is consistent with previous studies ( El Badawy et al, 2021 , Hu et al, 2021 ). After receiving FOE, it could be clearly observed that the anti-apoptosis capacity of gastric mucosa was enhanced, manifested in the recovery of Bcl-2 level and the control of Bax and Caspase-3.…”
Section: Discussionsupporting
confidence: 91%
“…Hu et al studied the protective effects of tilapia scales-purified collagen oligopeptides in specific pathogen-free (SPF) Sprague Dawley rats for 30 days [113]. The oral administration of collagen peptides significantly reduced gastric and duodenal ulcer index and MDA content.…”
Section: Antioxidant Effects Of Bioactive Peptides From Marine Animal...mentioning
confidence: 99%
“…The oral administration of collagen peptides significantly reduced gastric and duodenal ulcer index and MDA content. In comparison, increases in gastric juice pH and expressions of CAT, SOD, and glutathione peroxidase (GPx) were observed [113]. Furthermore, the oligopeptides purified from frigate tuna (Auxis thazard) showed hypouricemic properties.…”
Section: Antioxidant Effects Of Bioactive Peptides From Marine Animal...mentioning
confidence: 99%